Unravelling virtual realities: Gamers’ perceptions of the metaverse - Cruz, M.; Oliveira, A. (Electronics, 2024)
In a rapidly evolving digital landscape, the Metaverse emerges as a transformative force, integrating augmented reality, virtual reality, and the internet, to redefine online interactions. This collective virtual shared space promises to revolutionise global collaboration, communication, and information engagement. Our study consisted of the application, through an online form builder, of a questionnaire to Portuguese adult gamers, analysing the results with descriptive statistics. Our research question was: how is the Metaverse perceived and represented by gamers? In this context, we trace four objectives: (1) verify the representations of the Metaverse; (2) verify the representations of immersion; (3) verify the representations of the multiverse; and (4) verify the importance of these concepts in daily reality. Our findings explored the Metaverse, immersion, and multiverse concepts, uncovering gamers’ perceptions with emphasis on animation, gaming, and virtual worlds as foundational elements. The Metaverse arises as an evolving force that bridges emotional experiences, offering limitless possibilities for experimentation and exploration.